The Role of the SCO in the Process of Neutralizing Regional Challenges and Threats - E. G. Garbuzarova (Проблемы постсоветского пространства, 2022)
The Shanghai Cooperation Organization (SCO) is considered to be one of the key mechanisms for maintaining stability and security in Eurasia. Over the years of its existence the SCO gained considerable political weight and authority on the world stage. There are extremely pessimistic scenarios for the development of events in Afghanistan with the withdrawal of the United States Armed Forces from Afghanistan and the coming Taliban to power in this country in 2021. There is a high probability of aggravation of regional challenges and threats in the face of terrorism, drug smuggling, illegal migration, humanitarian catastrophe. Being an important element of the Eurasian security architecture the SCO has a good potential to counter these threats. Over the years of the SCO’s existence a solid legislative framework was developed within the organization and coordination mechanisms was created to counter regional threats. The national interests and security of the SCO member states are directly related to the situation in Afghanistan. That is why the Afghan issue is always on the agenda of the organization. Despite the emerging differences between the SCO member states on the Afghan issue a common position was developed at the anniversary summit of the organization in September 2021 in Dushanbe. All SCO members supported the solution of the Afghan problem through political and diplomatic means and stressed the need to form an inclusive government. The decision to accept Iran as a full member of the SCO was a significant event for the organization. As a full participant Iran became an additional advantage for the organization in solving regional problems. The factor of Iran which has a significant impact on the development of Afghanistan may become one of the key factors in building relations with the new Afghan authorities. Thus the SCO has a significant integration potential in the field of security and should play a positive role in the Afghan problem.